2017
DOI: 10.1002/dta.2326
|View full text |Cite
|
Sign up to set email alerts
|

Fatality involving ocfentanil documented by identification of metabolites

Abstract: The use of new psychoactive substances (NPS) has rapidly increased over the last decade. In the last 4 years, producers increasingly appear to be targeting non-controlled synthetic opioids, involving fentanyl derivatives such as ocfentanil (OcF). Identification of metabolites is of major importance in the context of NPS use, as it could improve the detection window in biological matrices in clinical and forensic intoxication cases. Hence, this work aims to report a fatality involving OcF documented by the iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…Although the utility of metabolite determination in biological samples is known, its application to authentic specimens is still scarce in the case of synthetic opioids due to the limited data available about their metabolism (Poklis et al, 2015 ; Staeheli et al, 2016 ; Martucci et al, 2017 ; Allibe et al, 2018 ). Recent publications about the identification of new metabolites of the synthetic opioids in vivo and in vitro are available (Wohlfarth et al, 2016 ; Steuer et al, 2017 ; Watanabe et al, 2017 ; Krotulski et al, 2018a ).…”
Section: Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the utility of metabolite determination in biological samples is known, its application to authentic specimens is still scarce in the case of synthetic opioids due to the limited data available about their metabolism (Poklis et al, 2015 ; Staeheli et al, 2016 ; Martucci et al, 2017 ; Allibe et al, 2018 ). Recent publications about the identification of new metabolites of the synthetic opioids in vivo and in vitro are available (Wohlfarth et al, 2016 ; Steuer et al, 2017 ; Watanabe et al, 2017 ; Krotulski et al, 2018a ).…”
Section: Metabolismmentioning
confidence: 99%
“…The analysis of metabolites in the different biological matrices may improve the interpretation of the results, extending the detection window and indicating if it was an acute or a delayed-death evaluating the metabolite-to-parent ratios. Recent publications about the identification of new metabolites of the synthetic opioids are available (Wohlfarth et al, 2016 ; Steuer et al, 2017 ; Watanabe et al, 2017 ; Krotulski et al, 2018a ); however, its application to authentic samples is still scarce (Poklis et al, 2015 ; Staeheli et al, 2016 ; Martucci et al, 2017 ; Allibe et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolites were identified in a two‐step investigative process; first with FS accurate mass analysis of the in vitro incubate and data mining for postulated metabolites, followed by targeted MS 2 analysis for any metabolites identified. Examination of the metabolism of fentanyl and other fentanyl‐analogues allowed the postulation of potential metabolites of CycP‐F . The possible pathways included N ‐dealkylation, amide hydrolysis, hydroxylation and potential sequential transformations.…”
Section: Methodsmentioning
confidence: 99%
“…Identification of target metabolites can therefore greatly increase the chances of detection of these drugs, as well as potentially extending the detection windows in biological matrices. In vitro metabolism studies, particularly followed up with analysis by liquid chromatography‐high resolution accurate mass analysis (LC‐HRAM) have been shown to be excellent tools for identifying potential target metabolites for analysis, with multiple NSOs already being subjected to such experiments . In vitro studies of NPS and addition of identified metabolites to a comprehensive accurate mass screening database allows for a rapid analytical response to the ever‐expanding problem of NPS.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Ohio, more than 4000 deaths were linked to opioids in 2016, with a 36% increase attributed to heroin and carfentanil abuse [11]. Since 2016, a number of deaths involving NSO have been reported in Europe: six fatalities involving ocfentanil have been reported in Belgium, Switzerland and France, and several cases of death due to carfentanil or another fentanyl analog have recently been described in the United Kingdom and Belgium [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%